Impairment of branchial energy transfer pathways in disease pathogenesis of Providencia rettgeri infection in juvenile Nile tilapia (Oreochromis niloticus): Remarkable involvement of creatine kinase activity - Baldissera M.D. (2019)
© 2018 Elsevier B.V.It is becoming evident that bacterial infectious diseases negatively affect gill energy metabolism, mainly because it causes alterations of enzymes that belong to the phosphotransfer network, such as creatine kinase (CK), adenylate kinase (AK) and pyruvate kinase (PK). Thus, the aim of this study was to evaluate whether the phosphotransfer network could be one pathway involved in the bioenergetic imbalance during Providencia rettgeri infection, as well as to investigate the bacteria's influence on adenosine triphosphate (ATP)-dependent enzymes. In this study, branchial cytosolic and mitochondrial CK activity decreased in infected animals on day 14 post-infection (PI) when compared to its respective control group. Moreover, branchial sodium-potassium pump (Na+/K+-ATPase) and proton-pump (H+-ATPase) activities decreased in infected animals on day 14 PI compared to the control. Finally, branchial thiobarbituric acid reactive substance levels increased in infected animals on day 14 PI, while non-protein thiol (NPSH) levels decreased. No significant difference was observed between groups regarding AK and PK activities. In summary, the impairment of CK activity elicited by P. rettgeri caused an impairment in branchial energetic homeostasis, reducing ATP availability in the gills. Moreover, inhibition of CK activity provokes an impairment of ATP-dependent enzymes, such as Na+/K+-ATPase and H+-ATPase, which can be mediated by lipid oxidative damage and reduction of NPSH content.